Critical review on Rasamanikya: An Ayurvedic mineral based formulation - PRITAM C. VAITY; VAISHALI M. KHOBRAGADE (International Journal of Pharma and Bio Sciences, 2019)
Rasamanikya is a mineral formulation mentioned in the chapter on Shwitraroga (Vitiligo) in Rasendrasara Sangraha, a classical Ayurveda text. Another classical text, Rasatangini, has also stressed upon the efficacy of Rasamanikya in Kushtharoga (skin disorders). However, the fact that Rasamanikya is prepared from Hartala, ie. Orpiment (an arsenic sulfide mineral), is fear evoking among some medical practioners and thus a probable cause for its marginal use in therapeutics. The present review explores Rasamanikya from all the aspects. To start with, the present review first provides an insight into the pharmaceutical and analytical aspect of Rasamanikya. Thereafter, the pre-clinical studies that include the in-vitro antimicrobial activity study and the in-vivo toxicity studies conducted on Rasamanikya have been discussed. And lastly, the clinical aspects of Rasamanikya have also been enlightened in this review. The classical and authoritative Ayurvedic Rasashastra literature, the scientific research papers and the relevant information on the internet have been used in this review. The present review also provides clues for further scientific studies on Rasamanikya.